Matematyka

Autorzy:A. Drążek, E.Duvnjak, Ewa Kokiernak-Jurkiewicz

Wydawnictwo:WSiP

Rok wydania:2016

Do wyrażenia 2x(3y-z+3x) dodaj trzykrotność wyrażenia x(-2x-z-2y) 4.67 gwiazdek na podstawie 9 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

Do wyrażenia 2x(3y-z+3x) dodaj trzykrotność wyrażenia x(-2x-z-2y)

5
 Zadanie
6
 Zadanie

7
 Zadanie

8
 Zadanie
9
 Zadanie
10
 Zadanie
11
 Zadanie
12
 Zadanie

`2x(3y-z+3x) + 3x(-2x-z-2y)= 6xy-2xz+6x^2-6x^2-3xz-6xy=-5xz`

`-5* (-1/5)*(-sqrt4)=1*(-2)=(-2)`